2019
DOI: 10.3390/toxins11050263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Relationships, Trichothecene Chemotype Diversity and Aggressiveness of Strains in a Global Collection of Fusarium graminearum Species

Abstract: Fusarium head blight (FHB), caused principally by the species belonging to the Fusarium graminearum species complex (FGSC), is an important disease in wheat, barley, and other small grain crops worldwide. Grain infected with species in the FGSC may be contaminated with trichothecene mycotoxins such as deoxynivalenol (DON) and nivalenol (NIV). In this study, we characterized the phylogenetic relationships, chemotype diversity, phenotypic characters, and aggressiveness of 150 strains in FGSC collected from eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…graminearum are segregating for 15ADON, 3ADON, and NIV worldwide [ 26 , 32 , 82 ] whereas the available data indicate the 15ADON chemotype is fixed in F . boothii [ 26 , 82 , 83 ]. Fusarium ussurianum , by contrast, appears to be fixed for the 3ADON chemotype in the Far East of Russia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…graminearum are segregating for 15ADON, 3ADON, and NIV worldwide [ 26 , 32 , 82 ] whereas the available data indicate the 15ADON chemotype is fixed in F . boothii [ 26 , 82 , 83 ]. Fusarium ussurianum , by contrast, appears to be fixed for the 3ADON chemotype in the Far East of Russia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with other reports that evaluated these species on other wheat cultivars including cv. Norm [ 6 , 11 , 41 , 83 ]. Even so, toxin analyses of the inoculated wheat heads revealed that these species were all toxigenic and made NIV in planta .…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium graminearum species complex isolates vary in their ability to cause disease in different hosts (Goswami and Kistler, ). In general, both 3ADON and 15ADON chemotypes of F. graminearum and F. asiaticum are more aggressive than NIV chemotypes of F. asiaticum , F. meridionale , and F. cortaderiae in wheat (Starkey et al , ; Spolti et al , ; Umpiérrez‐Failache et al , ; Liu et al , ; Nicolli et al , ; Yang et al , ; Amarasinghe et al , ). However, there have been few reports on the pathogenicity of FGSC isolates in rice (Goswami and Kistler, ; Lee et al , ; Gomes et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two viruses that share high sequence similarity with FgV1 or FgV2 have been recently isolated in China (hereafter referred to as FgV1-ch and FgV-ch9, respectively) ( Zhang et al, 2020 ). Considering that the original host strains of FgV1–4 belong to different lineages in the Fusarium graminearum species complex (FGSG), a complex that includes eight and several additional phylogenetic lineages that cause Fusarium head blight (FHB), the potential of adaptive evolution in FgVs can be inferred ( Amarasinghe et al, 2019 ). In this regard, the following question should be answered: Which evolutionary processes dominate FgV1 populations and consequently shape the structure and fitness of the populations?…”
Section: Introductionmentioning
confidence: 99%